The role of creativity and innovation in contemporary education - Milićević, Nebojša M.; Pejić, Biljana S.; Komlenić, Miroslav B. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
In this paper, there is the review of some of the most important admissions in the field of creativity and innovation in the context of development of contemporary education. Although it is very complex field, there is the tendency to see it as a major driving force of economic and social progress. The creativity is seen, at the same time, as the process and the product, and also as individual and general capability. The different approaches are not exclusive. That is the reason why the contemporary education can be approached from different aspects. On the other hand, the legal and other acts that have planned the development of creativity and innovation in education and the status in the practice, are analyzed critically. There is, also, taken in examination, the relationship of educational plans toward creativity and innovation in the sense of balance between : a) different fields b) different levels of education c)respect for the certain rules and free will d)individual interests and potentials of students. All the previous aspects are illustrated by the earlier research. Even though, there are positive results, the contemporary curriculum allow little space for the activities that could stimulate creative potential. It is necessary to plan the more creative forms of teaching in defining the various forms of education. The education and stimulation of teachers to apply innovative ways of teaching and new technologies could improve the process of studding and the advancement of the quality of teaching.